Variasi Higher Order Thingking Skills (HOTS) pada Soal USBN Bahasa Jawa di SMA Kesatrian 1 Semarang - Wahyuningsih, Tri; Utami, Esti Sudi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
The implementation of Higher Order Thinking Skills (HOTS) on Javanese Language National Standard School Exam Questions is needed to improve students' thinking power. HOTS’s question is not a difficult one but a matter of honing students' active abilities to create students who are able to think in a complex and deep way to solve a real problem. The research objectives are: (1) describe the implementation of HOTS about Javanese Language National Standard School Exam Questions in Senior High School 1 Kesatrian Semarang (2) describe the comparison of HOTS about Javanese Language National Standard School Exam Questions between 2017/2018 and 2018/2019 academic year. This study used a qualitative descriptive approach, data were collected using document study techniques. The results showed that the implementation of HOTS on the 2017/2018 and 2018/2019 USBN questions was distributed at the C4 cognitive level, the cognitive processes of "differentiating", "organizing", and "attributing". Cognitive level C5 "checks" cognitive processes, and cognitive level C6 "cognitive processes". In the Java language USBN problem, HOTS implementation in the cognitive process variations is still less varied. At the cognitive level C5 there is no "criticizing" cognitive process, while at the C6 cognitive level there are no cognitive processes of "formulating" and "planning".